Efficiency of geotextile filters in dewatering wastes (sludge) from water treatment works - Urashima, D. C. (2006)
This paper evaluates the efficiency of geotextile filters for sludge from a compact water treatment plant (WTP). The key aspects required in the methodology of selection and designing geotextile filters for sludge from dewatering was investigated based on laboratory tests results. The analyses were supported by the measured filtrated volume of water and turbidity resulting from variable head permeability tests carried out in two geotextiles and using the conventional granular filter (sand and gravel). The results of the present study showed that more than 75% of the dewatering sludge can be filtrated with low turbidity, which permits that this water can return to the treatment plan in order to be reuse in another cycle. The reduced volume of sludge retained by the geotextile that is transferred to the drying pound increases its efficiency by reducing the drying time. The low volume of the dry waste can be removed and the geotextile can be easily cleaned or replaced when needed. These procedures significantly reduce the volume of water needed in dewatering and also avoids waste discharges in the environment.